(untitled) (Revista Apotheke, 2021)
In discussions related to the concepts of art and education at school, John Dewey’s theory stands out. This philosopher contributed to the debate based on his historical and social perspectives, in search of the unity between theory and practice. This article aims to recall the thoughts Dewey brought about the concepts of art and education, from the experimental method and how the author thinks pedagogy is relevant for the development of democracy. Thus, qualitative relations between the concepts and the democratic ideal defended by the author have been established. Some historical, social and economic aspects that influenced the theorist to stand for a reflexive formation have been analyzed. The exposed analysis made the thought on the concepts of art and education possible in relation to his theory of democracy, based upon the experimental method. The conclusion was that it is embedded in his ideal of changing society, but it was characterized as the permanence of bourgeois principles.